2020
DOI: 10.24940/ijird/2020/v9/i2/feb20045
|View full text |Cite
|
Sign up to set email alerts
|

Business Strategies: An Antidote to Firm Profitability of Selected Flour Milling Companies in Nigeria

Abstract: The study of business strategies has drawn so much attention among business practitioners and academic researchers in the last two decades as globalization came fully into limelight. However, in Nigeria, there are few studies conducted to investigate the relationship between business strategies and firm profitability. This paper examined the effect of business strategies on profitability of selected flour milling companies in Nigeria. Data were collected through validated questionnaire administered to sixty ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…This result affirms the studies of Zipporah et al ( 2018) that strategies influence organizational performance positively to a great extent resulting in increased organization profitability, business turnover and volumes of sale. Falana et al (2020) also found that business strategies have significant and positive effect on profitability of firms. Similarly, Sajdak (2015), Esmail, and Seyed (2016) have explored the link between business strategies and firm profitability.…”
Section: Discussion Of Findingsmentioning
confidence: 88%
See 1 more Smart Citation
“…This result affirms the studies of Zipporah et al ( 2018) that strategies influence organizational performance positively to a great extent resulting in increased organization profitability, business turnover and volumes of sale. Falana et al (2020) also found that business strategies have significant and positive effect on profitability of firms. Similarly, Sajdak (2015), Esmail, and Seyed (2016) have explored the link between business strategies and firm profitability.…”
Section: Discussion Of Findingsmentioning
confidence: 88%
“…The result of the study carried out by Falana et al (2020), revealed that business strategies have significant positive effect on profitability. Adinan and Abukari (2013) carried out a study on the effect of product differentiation on profitability and found that there is a positive relationship between product differentiation and profitability.…”
Section: Business Strategies and Profitabilitymentioning
confidence: 99%